Number of polymorphonuclear leucocytes in the endocervical discharge smear examination as diagnostic test for chlamydial cervicitis - Satiti Retno Pudjiati Satiti Retno Pudjiati (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1997)
The chlamydial servicitis is the most prevalent sexually transmitted disease among child-bearing age women and usually asymtomatic in nature, so it is difficult to be diagnosed early and to be eradicated. The laboratory methods for supporting its clinical diagnosis, whether in vitro cultivation or automatic technique, are not only complicated but also expensive. The simplest laboratory testing, especially for primary clinical service with !imitated in laboratory equipment, is achieved by counting the total number of polymorphonuclear leucocytes of endoservical exudate. Unfortunately, the cut off point varied from one country to another. In Indonesia, this cut off point has not determined yet. The purpose of this study was to develop simple and efficient diagnostic test for diagnosing chlamydial cervicitis, by searching the cut off point of a number of polymorphonuclear leucocytes in the endocervical discharge smear examination stained with Gram. The subjects of this study were female sex workers; 44 were from the Clinic of Griya Lentera PKBI Yogyakarta and 36 were from Sanggrahan Resosialisation Yogyakarta. Gynecologic examination, laboratory examination with Gram staining and C. trachomatis antigen detection using Test Pack Chlamydia were done on all subjects. The results indicated that the cut off point of the number of polymorphonuclear leucocyte in diagnosing chlamydial cervicitis is 10 with 60 % sensitivity, 76.67 % specificity, 81 % PPV (positive predictive value) and 53.49 % NPV (negative predictive value).Key words: chlamydial cervicitis - Gram's stain - polymorphonuclear leucocyte - test pack chlamydia -female sex workers.